Myth of the strong leader : political leadership in modern age - Brown, Archie. 1938- (London : The Bodley Head, 2014)
"All too frequently, leadership is reduced to a simple dichotomy: the strong versus the weak. Yet, there are myriad ways to exercise effective political leadership -- as well as different ways to fail. We blame our leaders for economic downfalls and praise them for vital social reforms, but rarely do we question what makes some leaders successful while others falter. In this magisterial and wide-ranging survey of political leadership over the past hundred years, renowned Oxford politics professor Archie Brown challenges the widespread belief that strong leaders meaning those who dominate their colleagues and the policy-making process are the most successful and admirable."--Jacket.
Introduction -- Putting leaders in context -- Democratic leadership : myths, powers, styles -- Redefining leadership -- Transformational political leadership -- Revolutions and revolutionary leadership -- Totalitarian and authoritarian leadership -- Foreign policy illusions of 'strong leaders' -- What kind of leadership is desirable?
Includes bibliographical references (pages 367-438) and index.
Keywords: Political leadership -- History -- 20th century; Political leadership -- History -- 21st century; Politische Führung.